The Effect of Attitudes, Social Environment, and Self-Efficacy on Entrepreneurship Intention of S1 Management Students in West Jakarta - Vincent Gunawan; Andi Wijaya (International Journal of Application on Economics and Business, 2023)
Along with the passage of time and the development of people's ability in entrepreneurship, entrepreneurial activities are increasingly in demand by the world community from various different backgrounds including Indonesia. Entrepreneurial activities are now seen as an activity that can provide opportunities to achieve success through the efforts they create. The purpose of this study was to find out and analyze the influence of attitudes, sosial environment, and self-efficacy on the entrepreneurship intentions of S1 Management Students of West Jakarta. Sampling this study was done by non-probability sampling methods, namely voluntary sampling and data collection is done with questionnaires. This study sample was 100 respondents from 105 respondents who studied at universities in West Jakarta. This study used SmartPLS 3.3.3 in processing the collected data. The results of this study found that attitudes and self-efficacy have a positive and significant influence on entrepreneurship intentions in undergraduate management students in West Jakarta, while the social environment does not have a significant influence on the social entrepreneurship intentions of students.